Standar Profesionalisme, Independensi Auditor, dan Kualitas Audit Keuangan Pemerintah - Agusmadi Agusmadi; Muhammad Iqbal; Marzuki Marzuki; Azlim Azlim; Wiki Noviandi; Riza Ul Fahmi (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of applying professional auditing standards and auditor independence on the quality of government Financial Audits in the Regional Government Audit Institution. Using a quantitative descriptive-verificative method, data were collected through a Likert-scale questionnaire survey of 30 auditees from various regional government agencies. The results indicate that the research instrument is valid and reliable (Cronbach’s Alpha = 0.785), auditor independence significantly influences Audit Quality (p = 0.004), while professional standards have no significant partial effect (p = 0.249). However, simultaneously both variables significantly affect Audit Quality with a contribution of 44.2% (R² = 0.442), emphasizing auditor independence as the dominant factor in ensuring objectivity and accuracy of audit results. In conclusion, auditor independence must be continuously strengthened, while the application of professional standards remains essential to maintain consistency, in order to achieve transparent, accountable, and trustworthy government financial management.